Revision of South American stiletto fly genus Argolepida Metz & Irwin (Diptera: Therevidae: Therevinae) - Irwin, Michael E.; Winterton, Shaun L. (Zootaxa, 2021)
The stiletto fly genus Argolepida Metz & Irwin, 2003 is revised. Members of this genus are diminutive, yet distinctive, flies restricted to southern South America. Argolepida rivulosa (Kröber, 1928) is redescribed and seven new species are described and figured. A key to species is presented.